1990
DOI: 10.1002/1098-108x(199007)9:4<409::aid-eat2260090407>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Body-image disturbance in obesity

Abstract: It is accepted that obese individuals have a body-image (61) disturbance. We assumed that distorted size estimations are a characteristic 61 disturbance in the obese and that their 81 is on a developmentally lower level than in controls. The hypotheses were that in the obese there would be less differentiation between kinaesthetically and graphically expressed 51 and between BI and personality variables. The subjects were 74 obese and 66 nonobese women, matched in demographic variables. They were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Indeed, there are reasons to think that such distortions may generalise beyond touch entirely. Overestimation of body width has been reported in tasks involving proprioceptive localization of landmarks on the hand (e.g., Coelho et al, 2017;Ganea & Longo, 2017;Longo & Haggard, 2010) and face (e.g., Longo & Holmes, 2020;Mora et al, 2018), visual comparison judgments of hand size (e.g., Tamè et al, 2017), localization of body landmarks on a screen (e.g., Fuentes, Longo, et al, 2013a;Fuentes, Pazzaglia, Longo, Scivoletto, & Haggard, 2013b;Fuentes, Runa, et al, 2013c), and a range of body size estimation tasks from the eating disorders literature, such as the moving caliper method (e.g., Dolan et al, 1987;Halmi et al, 1977;Hundleby & Bourgouin, 1993), the adjustable light beam apparatus (e.g., Dolce et al, 1987;Thompson et al, 1986), kinesthetic judgments (e.g., Kreitler & Chemerinski, 1990), and the imagemarking procedure (e.g., Gorham & Hundleby, 1988;Thomas & Freeman, 1991). Some recent authors have suggested that analogous distortions may affect non-body objects (Peviani et al, 2021;Salvato et al, 2020;Saulton et al, 2014;Saulton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are reasons to think that such distortions may generalise beyond touch entirely. Overestimation of body width has been reported in tasks involving proprioceptive localization of landmarks on the hand (e.g., Coelho et al, 2017;Ganea & Longo, 2017;Longo & Haggard, 2010) and face (e.g., Longo & Holmes, 2020;Mora et al, 2018), visual comparison judgments of hand size (e.g., Tamè et al, 2017), localization of body landmarks on a screen (e.g., Fuentes, Longo, et al, 2013a;Fuentes, Pazzaglia, Longo, Scivoletto, & Haggard, 2013b;Fuentes, Runa, et al, 2013c), and a range of body size estimation tasks from the eating disorders literature, such as the moving caliper method (e.g., Dolan et al, 1987;Halmi et al, 1977;Hundleby & Bourgouin, 1993), the adjustable light beam apparatus (e.g., Dolce et al, 1987;Thompson et al, 1986), kinesthetic judgments (e.g., Kreitler & Chemerinski, 1990), and the imagemarking procedure (e.g., Gorham & Hundleby, 1988;Thomas & Freeman, 1991). Some recent authors have suggested that analogous distortions may affect non-body objects (Peviani et al, 2021;Salvato et al, 2020;Saulton et al, 2014;Saulton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%